Regular Physical Exercise Adherence Scale (REPEAS): a new instrument to measure environmental and personal barriers to adherence to regular physical exercise - Fábio Henrique Ferreira Pereira; Aldair Darlan Santos-; André Pontes-Silva; Renan Shida Marinho; Adriana Sanches Garcia-Araújo; Audrey Borghi-Silva; Maria Cláudia Gonçalves; Rita de Cássia Mendonça de Miranda; Jhonata Botelho Protazio; Cezar Augusto Brito Pinheiro; Almir Vieira Dibai-Filho; Daniela Bassi-Dibai (BMC, 2023)
Abstract Objective To create, develop, and validate a scale that identifies the environmental and personal barriers that make it difficult to adhere to the practice of physical exercise on a regular basis in a population of Brazilian adults. Methods We include adult individuals, aged 18-59 years, practitioners or former practitioners of physical exercise, with Brazilian Portuguese as their mother tongue. In the development and validation phases of the process, 6 specialists in the field of the health assessed the content validity: firstly, the specialists were asked to freely list the questions they would ask to investigate the barriers to adherence to regulating physical activity. Secondly, after compiling all the suggestions listed and eliminating suggestions with similar content, the items suggested in the first round were sent to the specialists so that an evaluation of all questions using a 5-point Likert scale and the content validity coefficient was calculated. We then evaluated the structural validity, construct validity, reliability, internal consistency, and ceiling and floor effects of the Regular Physical Exercise Adherence Scale (REPEAS). Results Sixteen items were proposed to measure the factors that make it difficult to adhere to the regular practice of physical exercise. The internal structure of the REPEAS initially tested was based on the theoretical proposal of creating the instrument with two domains. After the structural analysis, we used the modification indices to identify the redundant items of the instrument. Consequently, the final version of the REPEAS after factor analysis had 12 items. Thus, the structure with 2 domains and 12 items presented adequate fit indices. With regard to construct validity, the REPEAS scores were compared in two distinct groups: irregular practitioners/ex-practitioners versus regular practitioners of physical exercise, in which a significant difference could be observed between groups (p < 0.001) for both the domains. Acceptable reliability was observed for the environment and personal domains, with ICC values of 0.86 and 0.94, in the same order. For internal consistency, Cronbach's alpha value was 0.908 (environmental domain) and 0.915 (personal domain), these values being adequate for the REPEAS. Conclusion The REPEAS is a scale with a valid two-dimensional internal structure, consisting of 12 items, reliable and with a valid construct, which supports its use in the clinical, epidemiological, and research contexts in Brazil.